Trend analysis of temperature over the Meghalaya Plateau: A case study of Ri Bhoi District - Lyngdoh, Andy T.G; Purkayastha, Subrata (Acta Geographica Debrecina Landscape & Environment series, 2025)
Climate change is a reality in the present world, and most nations are fighting this menace by bringing in mitigation measures to check our carbon footprint and developing measures to make ourselves more resilient to hazards associated with climate change and global warming. These necessities measure the nature and degree of change in the climatic elements, viz., temperature, rainfall, etc. Located on the northern slopes of the Meghalaya plateau, the Ri Bhoi district is characterized by a complex climatic condition owing to its altitudinal differences. The district is divided into two distinct zones: the Highland zone, located closer to Shillong, and the Lowland zone, lying closer to the Brahmaputra plains. The economy of Ri Bhoi district is agrarian in nature, where most of the rural populations live close to nature, following subsistence agriculture with fewer technological innovations; hence, awareness of temperature changes becomes essential for carrying out their livelihoods. In this context, the present paper attempts to analyze both the minimum and maximum average monthly, seasonal, and annual temperatures over two decades (1999–2019) in both zones. The Mann-Kendall (MK) trend test and Sen’s slope estimate were employed to find the nature of the temperature trend and its magnitude in the two zones of Ri Bhoi District. The findings suggest an erratic behavior of both the maximum and minimum temperature has been observed in the Highland and Lowland zones of Ri Bhoi district over the past two decades, impacting agriculture and agro-based livelihoods.